TINJAUAN LEGAL NORMATIF FRANCHISE / WARALABA DI INDONESIA - Suryanto HP, Eddy (Universitas Slamet Riyadi, 2008)
Abstract To strengthen the economy of one country, it must be done by strengthening and accelerating industry and trade. The implementation of both activities, actually, can not be separated with export and import activities as well as to the service which create the relationship among the people who have different countries. The relationship can stay in harmony if the hardware of both activities and all its aspects can be accommodated by the appointment which is internationally designed. The aspect of the contract of franchise, object of law franchise can be seen from the subject of loan franchise, object of law franchise, the right and obligation of the parties, marketing area, the length of franchise business, the solution of the dispute, compensation, the way of paying the return, the creation, the guidance and the training to â€œthe franchiseeâ€ and the registration and the authority of issuing the STPUW. Keywords : legal normatif, franchise